The State of Evaluation in Canada - Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2004)
The article discusses the state of evaluation in Canada, highlighting the Canadian Evaluation Society and its publication, the Canadian Journal of Program Evaluation.